Political shock and international students: Estimating the “Trump effect” - Mingsi Song; Quan Li (Research & Politics)
The negative “Trump Effect” on international students has attracted wide media and scholarly attention. Surprisingly, the best existing evidence remains anecdotal and case-based. In this study, we fill this important gap. We employ a difference-in-differences (DID) design to estimate the Trump effect for the US vis-a-vis various control groups: top 5, top 10, top 20, and all other countries that compete with the US. We find a statistically significant and negative Trump effect that drives international students from the US to competing destinations. Relative to the top five competitors, about 12% fewer students came to the US during the first 3 years of the Trump Presidency. The average treatment effect is statistically significant across the top 5, top 10, and top 20 destination groups but not for the group of all other destinations as a whole. Pairwise DID estimates between the US and 91 individual countries further indicate that the Trump effect is primarily driven by 26 host nations. These findings contribute to our understanding of Trump effects, student flows, and migration.